Capture Hi-C reveals the influence on dynamic three-dimensional chromosome organization perturbed by genetic variation or vanillin stress in Saccharomyces cerevisiae - Wang, Xinning; Yang, Bolun; Zhao, Weiquan; Cao, Wenyan; Shen, Yu; Li, Zailu; Bao, Xiaoming (Frontiers in Microbiology, 2022)
Studying the mechanisms of resistance to vanillin in microorganisms, which is derived from lignin and blocks a major pathway of DNA double-strand break repair in yeast, will benefit the design of robust cell factories that produce biofuels and chemicals using lignocellulosic materials. A high vanillin-tolerant Saccharomyces cerevisiae strain EMV-8 carrying site mutations compared to its parent strain NAN-27 was selected for the analyses. The dynamics of the chromatin structure of eukaryotic cells play a critical role in transcription and the regulation of gene expression and thus the phenotype. Consequently, Hi-C and transcriptome analyses were conducted in EMV-8 and NAN-27 in log phase with or without vanillin stress to determine the effects of mutations and vanillin disturbance on the dynamics of three-dimensional chromosome organization and the influence of the organization on the transcriptome. The outcomes indicated that the chromosome interaction pattern disturbed by vanillin stress or genetic mutations in log phase was similar to that in mouse cells. The short chromosomes contact the short chromosomes, and the long chromosomes contact the long chromosomes. In response to vanillin stress, the boundaries of the topologically associating domain (TAD) in the vanillin-tolerant strain EMV-8 were more stable than those in its parent strain NAN-27. The motifs of SFL1, STB3 and NHP6A/B were enriched at TAD boundaries in both EMV-8 and NAN-27 with or without vanillin, indicating that these four genes were probably related to TAD formation. The Indel mutation of YRR1, whose absence was confirmed to benefit vanillin tolerance in EMV-8, caused two new interaction sites that contained three genes, WTM2, PUP1 and ALE1, whose overexpression did not affect vanillin resistance in yeast. Overall, our results revealed that in log phase, genetic mutations and vanillin disturbance have a negligible effect on three-dimensional chromosome organization, and the reformation or disappearance of TAD boundaries did not show an association with gene expression, which provide an example for studying yeast chromatin structure during stress tolerance using Hi-C technology.